Unraveling the Paradox of Housing Affordability: - Ramadhan, Wanda Dwi; Hazah, Hania Rizkieta; Djajanti, Atik; Mulyani, Susi Dwi (Journal of Accounting, Business and Management (JABM), 2025)
Housing affordability remains one of Indonesia’s pressing socioeconomics challenges, particularly for middle-to-lower income households whose income growth lags behind rising property prices. In response, the government introduced ministry of finance regulation (PMK) No. 13 of 2025, which provides a government-borne valueadded tax (VAT) incentive aimed at encouraging homeownership and stimulating the property sector. This study explores the perceived effectiveness of PMK 13/2025 in enhancing housing affordability by employing a policy analysis approach based on secondary data, including prior regulations, market reports, and academic literature. The findings indicate that while the incentive may improve consumer purchasing power, risks such as speculative price increases by developers and disproportionate benefits to investors remain. Furthermore, the limited scope of the policy applying only to new homes within a specific price range may reduce its reach among lower-income households. To maximize effectiveness, the policy requires stronger oversight and better integration with other housing subsidy schemes. The study underscores the importance of designing fiscal incentives that not only stimulate the housing market but also deliver equitable and sustainable benefits.